Exploration of Bacteria in Red Chili Plant Soil with Potential as Plant Growth Promoting Rhizobacteria (PGPR) - Miladiarsi Miladiarsi; Muhammad Rizal; Padil Wijaya (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Soil fertility depends on the availability of sufficient nutrients for plant absorption. Chemical fertilizers can be used to provide sufficient N and P, but this affects soil health. The presence of rhizobacteria act as biofertilizers by increasing nutrients and altering soil formation, especially in the phosphate and nitrogen cycles. Phosphate-solubilizing and nitrogen-fixing bacteria play a role in increasing soil fertility and improving unstable soil properties. This study aims to identify rhizobacteria that have the potential as PGPR to increase N and P levels in the soil. Soil samples were collected randomly at a depth of 10 cm around chili plant roots. Bacteria were isolated using serial dilution and cultured on Pikovskaya medium. A total of 27 isolates produced clear zones with the highest solubility index and were inoculated on Nitrogen-Free Bromthymol Blue Agar (NFB) to evaluate N fixation through a color change from green to blue, as well as hypersensitivity tests on tobacco plants. Isolates showing the highest P solubility, highest N fixation ability, and no necrosis in tobacco were inoculated into sterile soil to analyze compound changes. Soil N content was measured using the Kjeldahl method, while phosphate levels were analyzed using the Bray I and HCl methods. The results of the study showed that the addition of KE2.15 isolate to the soil after 4 weeks of application increased the total organic N and available P content, making it a potential biofertilizer.